2016
DOI: 10.1080/13548506.2016.1146404
|View full text |Cite
|
Sign up to set email alerts
|

Illness perception and quality of life of HIV-positive persons: mediation effects of tenacious and flexible goal pursuit

Abstract: Medical advances contribute to raise life expectancy of people living with HIV/AIDS (PLHIV). However, they still face challenges related to the disease, thus, quality of life (QOL) became a priority on the field. The self-regulatory model (SRM) guided this study. Illness perceptions (IP) are the beliefs, cognitions, representations of a disease, impacting PLHIV coping strategies and QOL. Tenacious goal pursuit (TGP) is the pursuit of goals with determination, flexible goal adjustment (FGA) is doing it with fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…The previous study had the same results, which showed that diabetic patients' illness perceptions affected their QoL (Mohamed et al, 2016). The present study supported the previous studies regarding the association between illness perception and QoL (Catunda, Seidl, & Lemétayer, 2017;Rahimi, baljani, & Zadgasem, 2012;Rawlings, Brown, & Reuber, 2017). Salemi, Hasemi, and Arefi (2016) also reported that illness perception in BIPQ domains significantly affected the QoL of SF-36 domain scores.…”
Section: Discussionsupporting
confidence: 81%
“…The previous study had the same results, which showed that diabetic patients' illness perceptions affected their QoL (Mohamed et al, 2016). The present study supported the previous studies regarding the association between illness perception and QoL (Catunda, Seidl, & Lemétayer, 2017;Rahimi, baljani, & Zadgasem, 2012;Rawlings, Brown, & Reuber, 2017). Salemi, Hasemi, and Arefi (2016) also reported that illness perception in BIPQ domains significantly affected the QoL of SF-36 domain scores.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies on different chronic illnesses have confirmed the mediating role of coping strategies in the relationship between illness representations and outcomes, such as mood, quality of life, and patients’ satisfaction (Diefenebach and Leventhal, 1996; Leventhal et al, 2001; Rutter and Rutter, 2002; Hagger and Orbell, 2003; Llewellyn et al, 2007; Gould et al, 2010; Catunda et al, 2016). However, some studies have suggested that illness representations are also directly associated with outcomes regardless of coping strategies, and that illness representations are more strongly associated with outcomes than coping strategies (e.g., Moss-Morris et al, 1996; Scharloo et al, 1998).…”
Section: Introductionmentioning
confidence: 98%
“…A body of work shows that goal adjustment predicts high levels of well-being in general and in the face of age-related developmental losses [ 5 , 6 ]. More precisely, FGA correlates positively with health perception, positive affect, life satisfaction, sense of control, positive self-evaluation, and low depression in old age [ 8 , 12 , 21 25 ]. In addition, FGA has been found to dampen the effects of age on depression [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%